Developing Kitab al-Mu‘in al-Mubin-Based Teaching Materials to Enhance Arabic Speaking Skills among Beginner Learners - Maulid Johansyah; Moh. Tohiri Habib (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
Arabic speaking instruction for beginner learners often faces a persistent gap between grammatical knowledge and oral communicative performance. Many learners are able to recognize vocabulary and understand Arabic rules, yet they still struggle to apply them accurately and confidently in spoken interaction. This study aims to describe the development of Kitab al-Mu‘in al-Mubin-based teaching materials and examine their effectiveness in enhancing Arabic speaking skills among beginner learners. The study employed a research and development design supported by quantitative and qualitative approaches. It was conducted at Al-Bahjah Islamic Boarding School, Cirebon, West Java, Indonesia, involving students from the second level of the tafaqquh program. Data were collected through interviews, questionnaires, and tests. The developed material integrated vocabulary support, functional grammar, introductory models, and applied oral examples to help learners connect linguistic knowledge with speaking practice. The effectiveness test involved an experimental group and a control group, each consisting of 45 students. The results showed that the experimental group achieved a higher mean score than the control group, with 84.7778 compared to 57.8889. The independent sample t-test indicated a significant difference between the two groups, with t = 15.229, df = 88, and Sig. (2-tailed) = .000. These findings demonstrate that Kitab al-Mu‘in al-Mubin-based teaching materials significantly improve beginner learners’ Arabic speaking skills. The study contributes to Arabic language pedagogy by offering a contextual model that integrates vocabulary, grammar, and guided oral practice in pesantren-based Arabic instruction.